Museum of Physical Education and Sports as a means of developing specialized historical knowledge among students - Shakhov, Artem A. (Физическое воспитание и студенческий спорт, 2023)
Formation of historical knowledge in the field of physical education and sports among students is an important task of physical education, sports, and professional training. Activity in this direction will improve the quality of educational work and patriotic education among students, form their understanding of social significance of the profession of a teacher and a coach, and increase motivation to achieve high sports results. Museum activities are an effective means of transferring historical physical culture and sports knowledge, but this approach has not been fully developed both from the theoretical and practical points of view. The purpose of the research is to study the means (potential) of sports museums in the formation of historical physical culture and sports knowledge among students in the process of their physical education, sports training, and professional education. Research method used are analysis of information sources on the topic under consideration, the activities of leading museums in Russia and abroad, and summarizing of many years of personal experience in organizing the work of a sports museum. At present, the museum is not only a place for obtaining, storing and exhibiting historical artifacts, but also a modern scientific, cultural, and educational facility. The main means of museum pedagogy are: museum excursions; project activities; development and participation in quests; preparing course projects, final qualifying papers and scientific articles; activities as a tour guide; exhibition preparation; creation of a museum website; working on the systematization of museum funds.